Estudo dos problemas de corte e empacotamento - Alvarez Martinez, David [UNESP] (2014)
In this work we study the cutting and packing problems with practical constraints that represent real world scenarios of the industry. The cutting problem consists in to cut a set of pieces from an object, and the packing problem consists in to pack a set of items in an object. In the real world there are a big number of variations of this problem. In this study we only carry out the problems where the pieces and the objects have a regular shape, bounding of that way the two-dimensional problems to use just rectangular items and the three-dimensional problems to use just parallelepiped pieces. Specifically, the cutting problems studied in this work are: the Two-Dimensional Single Knapsack Problem, taking into account cutting pattern constraints (guillotine and non-guillotine patterns), orientation of the pieces constraints, associated costs to the pieces constraints and demanding types of pieces constraints. The second problem that we work on is the Two-Dimensional Single Bin Size Packing Problem, taking into account cutting pattern constraints (only guillotine patterns) and orientation pieces constraints. The last problem is the Container Loading Problem (Three- Dimensional Single Large Object Placement Problem) taking into account: orientation box constraints, load-bearing strength constraints, cargo stability constraints (full support) and multi-drop constraints. All the previous problems have a big spectrum of application on the Industry, because of this; there is a big amount of previous work on it. Different methodologies, exact and approximate algorithms have been proposed as solution strategies. Due to the mathematical and computational complexity of these problems, the exact algorithms cannot solve real world instances of the problem. The approach of this study consists on presenting and/or adapting different encodings and optimization algorithms. Among the proposed approach solutions is ...